Going vertical: examining the rise and impact of contemporary Russian sports cinema - Crosson, Seán (Frontiers in Sports and Active Living, 2023)
This article will introduce a new database and online research platform (Sport in European Cinema, sportandfilm.eu) recently made publicly available which enables a deeper consideration of the significance of sport in European cinema, identifying salient aspects of the genre and its revealing engagement with European society and culture. In particular, drawing from the database findings and related research this article will examine the growing popularity and impact of sport cinema in the Russian context, above all from the early 2000s onwards. Indeed the third most commercially successful indigenous film ever released (as of 2023) at the Russian box office is a sports film. Such has the film’s impact being in Russia that it became an important part of the domestic discourse concerning Russia’s response to international criticism for both sporting and military actions over the past ten years. Indeed, this article will contend that Going Vertical also contributed to the grooming of a domestic audience for subsequent military actions (particularly in Ukraine), a process to which Russian sport cinema has made an important contribution. Through textual and contextual analysis, this paper examines the articulation and affirmation of existing power structures and ideological hegemony within Russian society as evident within Going Vertical and further recent Russian sport films in a particularly challenging period of national and international instability and contestation.